Enhanced Chitin Deacetylase Production Ability of Rhodococcus equi CGMCC14861 by Co-culture Fermentation With Staphylococcus sp. MC7 - Ma, Qinyuan; Gao, Xiuzhen; Tu, Linna; Han, Qi; Zhang, Xing; Guo, Yabo; Yan, Wenqin; Shen, Yanbing; Wang, Min (Frontiers in Microbiology, 2020)
Chitin deacetylase (CDA) can hydrolyze the acetamido group of chitin polymers and its deacetylated derivatives to produce chitosan, an industrially important biopolymer. Compared with traditional chemical methods, biocatalysis by CDA is more environment-friendly and easy to control. However, most reported CDAs show low fermentation yield and insufficient enzyme activity. Thus, the enhancement of CDA production has always been a challenge. In this study, we report co-culture fermentation to significantly promote the CDA production of Rhodococcus equi CGMCC14861 (ReCDA). Due to co-culture fermentation with Staphylococcus sp. MC7, ReCDA yield increased to 21.74 times that of pure culture of Rhodococcus equi. Additionally, the enhancement was demonstrated to be cell-independent by adding cell-free extracts and the filtrate obtained by 10 kDa ultrafiltration of Staphylococcus sp. MC7. By preliminary characterization, we found extracellular, thermosensitive signal substances produced by Staphylococcus that were less than 10 kDa. We investigated the mechanism of promotion of ReCDA production by transcriptomic analysis. The data showed that 328 genes were upregulated and 1258 genes were downregulated. The transcription level of the gene encoding ReCDA increased 2.3-fold. These findings provide new insights into the research of co-culture fermentation for the production of CDA and quorum sensing regulation.